2018
DOI: 10.1080/09593330.2018.1468486
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of grey water for non-potable purposes using pilot-scale solar photocatalytic tubular reactors

Abstract: Application of pilot-scale slurry-type tubular photocatalytic reactor was tested for the decentralized treatment of actual grey water. The reactors were fabricated by reusing the locally available materials at low cost, operated in batch recycle mode with 25 L of grey water. The influence of operational parameters such as catalysts' concentration, initial slurry pH and addition of HO on COD abatement were optimized. The results show that Ag-decorated TiO showed a two-fold increase in COD abatement than did pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Over a decade ago, the capacity for designing and constructing pilot-scale suspended photocatalytic systems was demonstrated where tubular reactors and parabolic concentrators were used for photocatalytic water detoxification (Figure a and b). More recently, Domen et al demonstrated the upscaling of their SrTiO 3 :Al photocatalyst panel into a 100 m 2 photocatalytic water-splitting reactor for H 2 generation containing 1600 panels . A maximum H 2 production rate of 3.6–3.7 mL/min (average 0.5% solar-to-hydrogen efficiency) was achieved under natural sunlight with solar radiation of approximately 0.9 kW/m 2 during autumn.…”
Section: Large-scale Systemmentioning
confidence: 99%
“…Over a decade ago, the capacity for designing and constructing pilot-scale suspended photocatalytic systems was demonstrated where tubular reactors and parabolic concentrators were used for photocatalytic water detoxification (Figure a and b). More recently, Domen et al demonstrated the upscaling of their SrTiO 3 :Al photocatalyst panel into a 100 m 2 photocatalytic water-splitting reactor for H 2 generation containing 1600 panels . A maximum H 2 production rate of 3.6–3.7 mL/min (average 0.5% solar-to-hydrogen efficiency) was achieved under natural sunlight with solar radiation of approximately 0.9 kW/m 2 during autumn.…”
Section: Large-scale Systemmentioning
confidence: 99%
“…Graywater is a highly reclaimable water source. Saran et al ( 2019 ) prepared TiO 2 ‐Ag for a pilot‐scale slurry‐type tubular photocatalytic reactor to treat actual graywater, with the addition of H 2 O 2 a 99% COD abatement was achieved within 2 h. Tsoumachidou et al ( 2017 ) used commercial TiO 2 ‐P25 with H 2 O 2 and Fe 3+ to treat graywater, which achieved an almost 64% DOC removal rate in a pilot‐scale slurry fountain photoreactor. Olga Sacco et al ( 2018 ) set a pilot‐scale test for real wastewater disinfection and MB removal using nitrogen‐doped TiO 2 particles (N‐TiO 2 /PS) immobilized on polystyrene spheres.…”
Section: Pilot‐scale Testsmentioning
confidence: 99%
“…A cost-effective slurry-type tubular photocatalytic reactor with the Ag-TiO 2 catalyst was tested at a pilot scale for its application in the decentralized treatment of gray water (Saran, Arunkumar, Manjari, & Devipriya, 2019). At an optimum operating condition (i.e., catalyst concentration of 220 ppm, initial pH of 2, and addition of 5 mM H 2 O 2 at a flow rate of 15 L under 1 mW/cm 2 solar irradiation), 100% organic pollutants were degraded, and 99% COD was removed within 2 hr, producing water available for various nonpotable use.…”
Section: Reactorsmentioning
confidence: 99%